X-ray diffraction and Rietveld characterization of radiation-induced physicochemical changes in Ariá (Goeppertia allouia) C-type starch. (August 2021) - da Costa Pinto, Camila; Sanches, Edgar Aparecido; Pedrosa Silva Clerici, Maria Teresa; Pereira, Márcio Tadeu; Campelo, Pedro Henrique; Michielon de Souza, Sérgio
Abstract: Extracted from a tuberous root of the Amazon forest named Ariá ( Goeppertia allouia ), starch samples were submitted to four γ-radiation doses of 1, 5, 20 and 50 kGy and investigated by powder X-ray diffraction (XRD) and pasting properties. The XRD patterns were quantified by the Rietveld refinement method and the pasting properties by Palabiyik's, Hill's and Arrhenius models. Crystallinity values were obtained considering the semi-crystalline microstructures (mean crystallites sizes and microstrains) and the weight fraction of the semi-crystalline phases were calculated considering the diffuse X-ray scattering. The combination of the techniques revealed that the increase in the amorphous component is related to the continuous degradation of the semi-crystalline phases in lower molecular weight sugars that also increased pasting temperature and delaying the gelation process. The reduction in the activation energy of the phase transition is associated with the accumulated energy in the defects, induced by γ-radiation. Graphical abstract: Image 1 Highlights: Starch from Ariá was subjected to γ-radiation and identified as C-type starch, composed of the A-type and B-type polymorphs. A new approach was proposed to quantify the phase content and crystallinity of starches using XRD and Rietveld method. The amorphous component increases with the growth of small sugar molecules generated by amylopectin chain breakage. The γ-radiation dose progressively influences the physicochemical properties of Ariá starch. Irradiation promoted partial dextrinization of the sample, influencing the physicochemical properties of the starch.